Demystifying Hawala: A Look into its Social Organization and Mechanics - Passas, Nikos (Journal of Scandinavian studies in criminology and crime prevention, 2006)
This paper sheds light on the routine practices and mechanics of hawala, an informal funds transfer system, which emerged in the Indian subcontinent and spread globally in recent decades. Hawala has come under suspicion of being a tool in the hands of al Qaeda and other terrorists, so a series of measures and policies have been taken internationally for its regulation and control. The paper dispels several myths about hawala, such as the lack of money movement or the absence of paper-work and trails for investigators. By focusing on the Pakistan hawala modus operandi, it also explains the routes money follows before it reaches the final destination mostly in the hands of expatriates' extended families. By showing how these mechanics make economic sense, the paper makes a contribution to more sensitive, informed, fair and consensual law enforcement